Desenvolvimento de método espectrofotométrico ambientalmente mais limpo para análise de nitrito em salsichas - Martins, Ângela Pinheiro [UNESP]; Luiz, Vitor Hugo Marques [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (My University, 2015)
A clean environmental spectrophotometric method for the analysis of nitrite using a new diazotizing reagent is reported. The proposed method is based on diazotization-coupling reaction between dapsone, nitrite and (naphthyl)ethylenediamine (NED) in phosphoric acid medium at room temperature. Experimental design methodologies were used to optimize the measurement conditions. The spectrophotometric measurements were carried out at 545 nm and the linear range obtained was 5.0 x 10-3-3 mg.L-1 -0.5 mg.L-1, with detection and quantification limits of 0.99 x 10-3-3 mg.L-1 e 3.31 x 10-3-3 mg.L-1, respectively. The proposed method was applied successfully to the analysis of nitrite in sausages and the results obtained by the proposed method were in good agreement with those obtained using the official method.
Development of a clean environmental spectrophotometric method for the analysis of nitrite in sausages
Keywords: Green Chemistry; Nitrite; Sausage